2021
DOI: 10.1007/s00394-021-02736-4
|View full text |Cite
|
Sign up to set email alerts
|

Lignan exposure: a worldwide perspective

Abstract: Dietary lignans are phytoestrogens that are mostly found in plant-based foods, especially whole grains, seeds, nuts, legumes and vegetables. An accurate assessment of lignan exposure is crucial to evaluate their potential health benefits and to establish future recommendations and dietary guidelines. This narrative review aimed to (i) summarize the pros and the cons of the current main assessment methods for lignan exposure─i.e., dietary questionnaires, food composition tables and biomarkers, (ii) describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 148 publications
(138 reference statements)
0
8
0
Order By: Relevance
“…Considering that there are differences in the food types consumed by the population in different regions, the intakes of lignans are also different. Currently, data on dietary intake of lignans are mainly available for several European countries . A study conducted with 4660 Dutch adults (aged 19–97 years) revealed that the mean intake of lignan was 979 μg.…”
Section: Lignans Sources and Intakementioning
confidence: 99%
See 1 more Smart Citation
“…Considering that there are differences in the food types consumed by the population in different regions, the intakes of lignans are also different. Currently, data on dietary intake of lignans are mainly available for several European countries . A study conducted with 4660 Dutch adults (aged 19–97 years) revealed that the mean intake of lignan was 979 μg.…”
Section: Lignans Sources and Intakementioning
confidence: 99%
“…Dietary habits may account for the differences in plasma ENL and END levels. Many studies on diet use whole grains, seeds, or fruits as a food source of lignans . Research has revealed that in almost all subjects, dietary intervention with lignan-rich foods (mostly flaxseed and sesame) can increase the level of ENL in the blood. , Food is a complex system, and lignans in food may act synergistically with other components.…”
Section: Digestion Absorption and Transformation Of Lignan In Vivo An...mentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21] Most previous studies used the food frequency questionnaire (FFQ) to estimate habitual intake of plant foods, [11][12][13]21 which may have been subject to measurement errors. In addition, food composition tables/databases on lignans were not complete, 22 which could have undermined the accuracy of the estimation of dietary lignan intake. Moreover, the bioavailability of lignans can be determined by not only the dietary intake levels but also many other factors such as genetic variations and the host gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Persons with different gut microbiota compositions may have different capacities for producing enterolignans. [22][23][24][25] Although conventional culture-based studies identified multiple bacterial genera capable of metabolizing lignans into enterolignans, 23,[26][27][28][29][30] these studies may not have considered all microbes that contribute to the production of enterolignans, given the known difficulties in culturing many of the microbes comprising the human gastrointestinal microbiome. Also, the evidence may not be applied to general populations, because the human diet is complex, and the gut microbial ability to produce enterolignans depends not only on microbial compositions but also on the habitual diet consumed.…”
Section: Introductionmentioning
confidence: 99%
“…Plant lignans (e.g., pinoresinol, lariciresinol, and secoisolaricilesinol) are polyphenols that are present in various dietary sources (e.g., flaxseed, sesame, and sunflower seeds) and widely consumed worldwide [14]. Plant lignans are converted to enterolignans (enterodiol [ED] and enterolactone [EL]) through their intermediates, such as secoisolariciresinol (SECO) and didemethyl−SECO [15][16][17].…”
Section: Introductionmentioning
confidence: 99%